The Devils We Know - Morone, James A., 1951- (Book collections on Project MUSE., 2014)
"Is there an American culture? Certainly, says James Morone. Americans are fighting over it now. They have been fighting over it since the first Puritan stepped ashore. Americans hate government (no national health insurance!) and call for more of it (lock 'em up!). They prize democracy (power to the people) and scramble to restrict it (the electoral college in the 21st century?). They celebrate opportunity--but only for some (don't let those people in!). Americans proclaim liberty then wrestle over which kind--positive (freedom from want) or negative (no new taxes!)? In this volume Morone offers his own answer to the conundrum of American political culture: It is a perpetual work in progress. Immigrants arrive, excluded groups demand power, and each generation injects new ethnicities, races, religions, ideas, foods, entertainments, sins, and body types into the national mix. The challengers--the devils we know--keep inventing new answers to the nation's fundamental question: Who are we? Each essay in The Devils We Know takes up a different aspect of the creative conflicts that shape America. Ranging from Huck Finn to Obamacare, Morone explores the ways in which culture interacts with other forces--most notably the rules and organizations that channel collective choices. The battle to define the nation's political culture spills over into every area of American life, but three are especially important: democracy, economics, and morals--each, in turn, complicated by race, race, race. Written over 25 years, these essays constitute a closely observed and deeply thoughtful vision of what America is--its ideas, images, rules, institutions, and culture clashes. Together, they explain just why America is the way it is. And what it might become"--